A review on bus protocols and conversion/translator between different protocols. Issue 8 (17th November 2019) - Akshaykumar, Naorem; Adhikari, Shuma; Singh, Loitongbam Surajkumar
Abstract: A computer consists of different components/modules and different communication protocols are used among them. These protocols are needed to achieve the interoperability between two devices/modules. Different protocols cannot communicate directly, there is a need for conversion. A protocol converters block is needed. These compact protocol converters create low power, low voltage connection as well as smaller chip area, making it easy to add multiple devices or components. This paper give a brief description of some commonly used bus protocols such as Serial Peripheral Interface (SPI), Inter-Integrated Circuit (I2C), Advanced Microcontroller Bus Architecture (AMBA), Universal Serial Bus (USB), Peripheral Component Interconnect Express (PCIe) and Ethernet. A review of some protocol converter/translator are done with a view to explore their usability.